Carbon nanotubes of oil fly ash as lubricant additives for different base oils and their tribology performance. Issue 64 (17th August 2017) - Salah, Numan; Abdel-wahab, M. Sh.; Alshahrie, Ahmed; Alharbi, Najlaa D.; Khan, Zishan H.
Abstract : CNTs of oil fly ash were found to be suitable as lubricant additives for Aramco base oil. Abstract : Oil fly ash has been reported to be a good source for the production of carbon nanotubes (CNTs). Recently, these CNTs were evaluated as lubricant additives in sunflower base oil and were found to exhibit excellent tribological properties. In this work, these CNTs were tested as lubricant additives in 100SN, 500SN and 150BS Saudi Aramco base oils. The results on other commercial carbon nanostructures like multiwall and single wall CNTs and graphene are also included in this study for comparison. Excellent tribological performance was obtained with CNTs of fly ash at a very small concentration. The observed reduction in values of the friction coefficient between two metallic surfaces using these CNTs was found to be superior to those of other carbon nanomaterials. The value of the friction coefficient was reduced by around 20% at a concentration of 0.1 wt%. These values were also investigated as a function of load, speed and temperature. The rheological behaviour showed that the viscosity of the 0.1 wt% CNTs-impregnated 500SN oil is almost invariant compared to that of the pure one. It is therefore suggested that CNTs of fly ash may be a good lubricant additive to minimize the friction and improve the fuel economy.